Yerba Mate as a Source of Elements and Bioactive Compounds with Antioxidant Activity - Elżbieta Rząsa-Duran; Agata Kryczyk-Poprawa; Dawid Drabicki; Adrian Podkowa; Katarzyna Sułkowska-Ziaja; Agnieszka Szewczyk; Katarzyna Kała; Włodzimierz Opoka; Piotr Zięba; Maciej Fidurski; Bożena Muszyńska (MDPI AG, 2022)
Ilex paraguariensis (yerba mate) is a plant species of the holly genus Ilex native to South America from the family Aquifoliaceae and is used for the production of yerba mate infusion. The leaves of the plant are steeped in hot water to make a beverage known as mate. The present study aimed to quantify and compare the content of selected elements in dried leaves and stems of I. paraguariensis (originating from Paraguay, Argentina, and Brazil) available in the market in Poland and determine the amount of these elements and bioactive compounds that pass into the infusion prepared from them. The contents of the following antioxidant compounds were assessed: neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, caffeic acid, 4-feruloylquinic acid, isochlorogenic acid, rutoside, astragalin, caffeine, and indole derivatives. All the tested samples showed the presence of elements such as magnesium, zinc, copper, iron, and manganese. The highest antioxidant activity was determined for infusion prepared from yerba mate samples from Brazil. Drinking approximately 1 L of the infusion a day will partially cover the daily requirement of these elements and bioactive compounds. The highest content of organic compounds with antioxidant properties (phenolic compounds and caffeine) was found in yerba mate infusions from Brazil.